Physiological characterization and proline route genes quantification under long-term cold stress in Carrizo citrange - Primo-Capella, Amparo; Martínez-Cuenca, Mary-Rus; Gil-Muñoz, Francisco; Forner-Giner, María A. (Elsevier, 2021)
Low temperature is one of the abiotic stresses that most limits crop production, growth and distribution. Currently climate change weather alters temperature worldwide, which produces both high and low temperatures. This work aimed to know how citrus responds to long-term low temperatures after being submitted to 1 °C day-night during six weeks. Physiological parameters were analyzed and it was obtained that photosynthesis and growth drastically decreased, water potential increased and osmotic potential did not change. Fv/Fm (maximum quantum yield of PSII) lowered, and degradation of chlorophylls a and b took place.